2010
DOI: 10.1073/pnas.1012669107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxytocin on recollections of maternal care and closeness

Abstract: Although the infant-caregiver attachment bond is critical to survival, little is known about the biological mechanisms supporting attachment representations in humans. Oxytocin plays a key role in attachment bond formation and maintenance in animals and thus could be expected to affect attachment representations in humans.To investigate this possibility, we administered 24 IU intranasal oxytocin to healthy male adults in a double-blind, placebo-controlled, crossover designed study and then assessed memories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
134
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(160 citation statements)
references
References 32 publications
16
134
2
2
Order By: Relevance
“…Notably, perception of attachment security was improved after OT administration in healthy male students (Buchheim et al, 2009). However, opposite effects of OT administration on attachment have also been found: anxiously attached healthy males remembered their mother as less caring after OT administration, compared with placebo (Bartz et al, 2010). In addition, OT administration in anxiously attached BPD patients and healthy controls decreased cooperation and trust (Bartz et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Notably, perception of attachment security was improved after OT administration in healthy male students (Buchheim et al, 2009). However, opposite effects of OT administration on attachment have also been found: anxiously attached healthy males remembered their mother as less caring after OT administration, compared with placebo (Bartz et al, 2010). In addition, OT administration in anxiously attached BPD patients and healthy controls decreased cooperation and trust (Bartz et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Recent behavioural genetics studies have identified specific genes, such as the oxytocin receptor polymorphism (OXTR) and the catechol-O-methyltransferase (COMT), with behavioural phenotypes related to intergroup conflict contagion, such as empathy and altruistic behaviour [55][56][57][58]. Population allelic frequency variation is apparent in a number of genetic functional polymorphisms important to social behaviour [54,59].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that oxytocin plays an important role in social interactions (Bartz et al, 2010;Lim and Young, 2006). Deficits in social functioning observed in psychiatric disorders including schizophrenia (Couture et al, 2006;Sparks et al, 2010) and mood disorders (Inoue et al, 2004;Montag et al, 2010;Wolkenstein et al, 2011) imply the possible involvement of oxytocin in the pathophysiology of these disorders.…”
Section: Introductionmentioning
confidence: 99%